2012
DOI: 10.1371/journal.pntd.0001653
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Isolation and Confirmation of Crimean-Congo Hemorrhagic Fever Virus in Human, Ticks and Animals in Ahmadabad, India, 2010–2011

Abstract: BackgroundIn January 2011, human cases with hemorrhagic manifestations in the hospital staff were reported from a tertiary care hospital in Ahmadabad, India. This paper reports a detailed epidemiological investigation of nosocomial outbreak from the affected area of Ahmadabad, Gujarat, India.Principal FindingsSamples from 3 suspected cases, 83 contacts, Hyalomma ticks and livestock were screened for Crimean-Congo hemorrhagic fever (CCHF) virus by qRT-PCR of which samples of two medical professionals (case C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 14 publications
1
85
0
Order By: Relevance
“…In early 2011, the first cases of CCHF were identified in India, in a nosocomial outbreak in Gujarat state, which adjoins Pakistan (Mishra et al, 2011). A recent serosurvey and sampling of H. anatolicum ticks showed that infection was present in local livestock (Mourya et al, 2012).…”
Section: Cchf In Eastern and Central Asiamentioning
confidence: 99%
“…In early 2011, the first cases of CCHF were identified in India, in a nosocomial outbreak in Gujarat state, which adjoins Pakistan (Mishra et al, 2011). A recent serosurvey and sampling of H. anatolicum ticks showed that infection was present in local livestock (Mourya et al, 2012).…”
Section: Cchf In Eastern and Central Asiamentioning
confidence: 99%
“…In this context, it will be an invaluable new tool in studying specific antibody responses induced by the many novel CCHFV vaccine candidates currently undergoing research and development (5,24,25). It is known that CCHFV infects various wild and domestic animals, such as cattle, sheep, goats, buffalo, hares, squirrels, mice, rats, and hedgehogs (26)(27)(28)(29). While further studies are necessary before utilizing the assay for animal sera, the neutralization assay reported in this study does have potential as a sero-epidemiological tool that can be used to accurately detect CCHFV infections in animals.…”
Section: Resultsmentioning
confidence: 99%
“…In this outbreak among 76 reported cases, four human deaths were occurred in which the first death was of a 32-year old housewife on 3 rd January, 2011 in a Korat village of Sanand, and on 13 th January, 2011 a 35-year old doctor treating her died, and on 18 th January, 2011 an accompanying nurse also died (Mourya et al, 2012). The following villages were affected seriously during outbreak of CCHF in Gujarat -Moraiya (13 cases), Shela (6 cases), Changodhar (23 cases), Navapur-Vaghajipuar (13 cases), Dholeshwar (5 cases), Kolat (9 cases), Motidevti (1 case) and Telav (6 cases) (Ministry of Health and Family Welfare, 2011).…”
Section: Epidemiologymentioning
confidence: 94%
“…Rodent samples were also sent to the HSADL laboratory in Bhopal. The CCHF virus was found in high quantities in ticks (Mourya et al, 2012). National Centre for Disease Control, New Delhi developed the polymerase chain reaction (PCR) primers for the testing of the samples.…”
Section: Epidemiologymentioning
confidence: 99%